2014
DOI: 10.1039/c3ja50389e
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of single- and multivariate calibration for determination of Si, Mn, Cr and Ni in high-alloyed stainless steels by laser-induced breakdown spectrometry

Abstract: Overcoming the matrix effect in LIBS analysis of high-alloyed stainless steel by specifying the temporal parameters of signal registration and multivariate calibration based on PCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…At room temperature, Li 15 Si 4 has been proposed as the fully lithiated phase of Si, leading to a maximum capacity of 3579 mAh g −1 and a volume expansion of 280% . The discharge and charge potentials of Si are ≈0.2 and 0.3–0.5 V with respect to Li/Li + , respectively.…”
Section: Si For Libsmentioning
confidence: 99%
“…At room temperature, Li 15 Si 4 has been proposed as the fully lithiated phase of Si, leading to a maximum capacity of 3579 mAh g −1 and a volume expansion of 280% . The discharge and charge potentials of Si are ≈0.2 and 0.3–0.5 V with respect to Li/Li + , respectively.…”
Section: Si For Libsmentioning
confidence: 99%
“…Therefore, it is reported that LIBS has suffered the influence of self-absorption, which caused a decrease in the slope of the calibration curve. 37,44,45 Obviously, the measurement results are less affected by self-absorption using long–short DP-LIBS. It can be attributed to the stabilization effect of a long pulse.…”
Section: Calibration Curvesmentioning
confidence: 99%
“…The input variable of PLS can be characteristic spectral lines [42], partial spectral region [43] or full spectrum [44]. Amador-Hernandez et al [45] used PLS-1 to quantify gold and silver gold and silver in Au-Ag-Cu alloys.…”
Section: Calibration and Validation Of Analytical Methods -A Samplingmentioning
confidence: 99%